(untitled) (Italian Review of Legal History, 2015)
Mutual influences between France and Italy in the field of law have been constantly present in both directions since the middle ages. Some examples are briefly recalled: Feudal law, born in Carolingian kingdom and settled in written form in Lombardy two centuries later; the new legal science of the bolognese Glossators of the XII Century, early adopted and developed in new directions in Provence and Languedoc; the Orléans School of Law of the XIII Century, at the origins of the Commentators School flourished in Italy in the XIV Century; the Humanistic School of Law, whose approach Alciatus helped to establish in Bourges, reaching its climax in France in the XVI Century; the new doctrines of the French philosophes and of the milanese Beccaria in the XVIII Century; the French codification and administrative order estblished by Napoleon and largely adopted in Italy in the XIX Century. Grafts and osmosis are constant features of the european legal history.